Peran Agility, Disiplin Kerja, Komunikasi Skill dan Kecerdasan Intelektual Terhadap Kinerja Karyawan BPR-BKK Demak - Sukardi Sukardi; Siti Aminah (Forum Kerjasama Pendidikan Tinggi, 2022)
The purpose of the study was to analyze the role of agility, work discipline, communication skills and intellectual intelligence on the performance of BPR-BKK Demak Regency employees. The population in this study were employees of PT. BPR BKK Demak Regency with a total of 148 people. The sampling technique used in this study was proportionate stratified random sampling. Determination of the number of samples in this study was determined by the Slovin formula obtained by 60 respondents. Sources of data using primary data with data collection method using a questionnaire. Data analysis used linear regression analysis. The results of agility research have a positive and significant effect on the performance of BPR-BKK employees in Demak Regency. Work discipline has a positive and significant effect on the performance of BPR-BKK employees in Demak Regency. Communication skills have a positive and significant effect on the performance of BPR-BKK employees in Demak Regency. Intellectual intelligence has a positive and significant effect on the performance of BPR-BKK Demak Regency employees.